Bibliometric Analysis of Public Policy Research in Indonesia 2011-2021 - Azwar Aswin; Madya Putra Yaumil Ahad; Metha Claudia Agatha Silitonga; Rori Gusparirin (Journal of Local Government Issues (LOGOS), 2022)
The aim of this study was to analyze the bibliometric characteristics of research works on public policy in Indonesia during the last ten years (2011-2021) by foreign and Indonesian authors. This study utilized Scopus database and retrieved 128 scientific publications from international authors focusing on public policy in Indonesia. The publications are examined based on several indicators including: publication trends, contribution of countries, journals, institutions, authors, top cited articles, and keyword analysis. The results show that during the last decade, there has been significant growth in the number of publications, with Indonesia as the country with the most published research works. Meanwhile, the influential institution affiliations publishing works about public policy in Indonesia are University of New South Wales, Australia and Vanderbilt University from the United States. Besides that, the top influential journal publishers are Development in Practices (UK) and Forest Policy and Economics (Netherlands). Based on the number of publications, Indonesian authors hold the top position, meanwhile, foreign authors were identified as the writers with the largest number of article citations. The most-cited article in public policy research in Indonesia focuses on education policy and published in International Journal of Educational Development. However, four of the top ten articles with the most citations are published in Forest Policy and Economics.